2008
DOI: 10.1002/star.200700698
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Guar and Wheat Bran on the Physical and Nutritional Quality of Extruded Breakfast Cereals

Abstract: Two non-starch polysaccharides, guar gum and wheat bran, were used at 15% replacement level in a cereal base to produce an extruded breakfast cereal product from both wholemeal and high-ratio wheat flour mixes. The inclusion of the non-starch polysaccharides into the flour bases had no significant effect on the expansion ratio of the products. However, the product density and bulk density of the extruded products increased with guar gum and wheat bran addition. The pasting properties of the raw flour and polys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
93
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(103 citation statements)
references
References 23 publications
8
93
1
1
Order By: Relevance
“…doi:10.1016/j.foodchem.2010.05.071 lubricating effect on the melt. This interferes with the air cell formation and limits the starch gelatinisation required for expansion of the snacks, as a result the snacks will be less expanded and hard in texture (Ainsworth, Ibanoglu, Plunkett, Ibanoglu, & Stojceska, 2007;Brennan, Merts, Monro, Woolnough, & Brennan, 2008;Camire, 1998;Yanniotis, Petraki, & Soumpasi, 2007). To compensate, severe extrusion processing at high temperature and shear is needed to decrease the melt viscosity and produce well expanded products enriched with tomato derivatives (Altan, McCarthy, & Maskan, 2008;Huang, Peng, Lu, Lui, & Lin, 2006;Yagci & Gogus, 2008).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…doi:10.1016/j.foodchem.2010.05.071 lubricating effect on the melt. This interferes with the air cell formation and limits the starch gelatinisation required for expansion of the snacks, as a result the snacks will be less expanded and hard in texture (Ainsworth, Ibanoglu, Plunkett, Ibanoglu, & Stojceska, 2007;Brennan, Merts, Monro, Woolnough, & Brennan, 2008;Camire, 1998;Yanniotis, Petraki, & Soumpasi, 2007). To compensate, severe extrusion processing at high temperature and shear is needed to decrease the melt viscosity and produce well expanded products enriched with tomato derivatives (Altan, McCarthy, & Maskan, 2008;Huang, Peng, Lu, Lui, & Lin, 2006;Yagci & Gogus, 2008).…”
Section: Introductionmentioning
confidence: 94%
“…Product density: The product density was determined by the poppy seed displacement method applied to 1 l of extruded products (Brennan et al, 2008). Variation in the product density of the product is largely dependant on the proportion of voids or bubbles that were trapped in the extruded products as they solidified from the extruder.…”
Section: Physical Propertiesmentioning
confidence: 99%
“…The influence of fibre on the carbohydrate digestibility and postprandial blood glucose levels has been brought to light in many in vitro studies Brennan & Samyue, 2004;Brennan et al, 2012;Brennan et al, 2008) and human studies (Cummings et al, 1996;Raben et al, 1994;Reader et al, 1997;Wisker & Feldheim, 1990;Wisker et al, 1992).…”
Section: Dietary Fibre and Glycemic Impactmentioning
confidence: 99%
“…The method employed by Brennan et al (2008) in determining in vitro carbohydrate digestibility was used. Two grams of previously cooked and minced spaghetti were mixed with 30 mL of distilled water and 0.8 mL of 1 M HCl to achieve a pH of 2.5.…”
Section: In Vitro Carbohydrate Digestionmentioning
confidence: 99%
“…Brennan et al [62] evaluated the effects of the addition of dietary fiber (wheat bran, guar gum, inulin, hi-maize, and swede) at different concentrations (5-15%) and found that peak and final viscosities among the different extruded products increased with the addition of guar gum. Guar gum decreased readily digestible starch, being more effective than wheat bran.…”
Section: Starch-galactomannan System In Extrusion Cookingmentioning
confidence: 99%